Exploring salivary biomarkers and swallowing perceptions in Sjogren's syndrome: A case–control feasibility study. Issue 3 (16th September 2022) - Letawsky, Veronica H.; Holman, Parker J.; Nguyen, Caroline T.; Dawson, Camilla; Weinberg, Joanne; Williams, Lynne J.; Skoretz, Stacey A.
Abstract: Background: The autoimmune disease Sjogren's syndrome (SS) is often characterized by salivary changes that may affect swallowing. No known study has investigated the association between salivary biomarkers and perceptions of swallowing in individuals with SS. Our objectives were to explore: (1) the operational feasibility of investigating saliva volume and composition, along with perceptions of swallowing, in those with and without SS; and (2) the relationship between saliva composition and perceptions of oral dryness, swallowing, and quality of life. Methods: We conducted a prospective, case–control feasibility study, collecting feasibility data (recruitment rate and optimal saliva collection methods) and whole mouth saliva samples (unstimulated and stimulated). We measured total protein content and conducted sialochemical (α‐amylase, cortisol, C‐reactive protein [CRP], and mucins), sialometric (flow rate), and perceptual (oral dryness and swallowing‐related quality of life [SWAL‐QOL]) assessments. Our exploratory analyses focused on the main and fixed effects. We summarized all data descriptively, comparing: (a) outcomes between groups ( t tests or Mann–Whitney U ) and (b) salivary and perceptual data across participants (partial least‐squares correlation [PLSC]). Results: We enrolled 12 ( N ) participants (6 per group), all providing analyzable saliva. Cases had lower flow rate ( p = 0.003) and higher total protein, cortisol, and CRP concentrations ( p < 0.02) than controls. PLSC revealed inverse covariance between sialochemical and SWAL‐QOL data across participants. Conclusion: Our study was feasible as designed. We explored novel relationships between salivary outcomes and participant‐reported perceptions, distinguishing individuals with and without SS. Our findings support further study of saliva's role in perceptions of swallowing, specifically analytes with lubricative properties. Abstract : We distinguished novel relationships between salivary properties and participant‐reported perceptions of swallowing in those with and without Sjogren's syndrome. Our findings support the feasibility of further study of saliva's role and analytes with lubricative properties during swallowing. Utilizing salivary investigations along with other swallowing diagnostics, salivary analyte profiling may enable biomarker‐based diagnostic and treatment approaches for dysphagia and autoimmune diseases. Key points: Our successful feasibility study distinguished individuals with and without Sjogren's syndrome (SS) according to novel relationships between salivary properties and participant‐reported perceptions of swallowing. Salivary analyte profiling in SS may enable biomarker‐based approaches to early identification, differential diagnosis, and bespoke treatment of dysphagia, while also informing the diagnostic process for SS and other chronic, autoimmune conditions.